2018
DOI: 10.1371/journal.pone.0208593
|View full text |Cite
|
Sign up to set email alerts
|

Low dose aspirin blocks breast cancer-induced cognitive impairment in mice

Abstract: Cancer patients with non-central nervous system tumors often suffer from cognitive impairment. While chemotherapy has long been attributed as the cause of these memory, learning and concentration difficulties, we recently observed cognitive impairment in cancer patients prior to treatment. This suggests the cancer alone may be sufficient to induce cognitive impairment, however the mechanisms are unknown. Here, we show that we can experimentally replicate the clinical phenomenon of cancer-associated cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 50 publications
2
41
1
Order By: Relevance
“…The role of inflammation in Alzheimer disease (AD) and some psychological disorders has been studied much deeper than in other fields (Heppner et al et al, 2015;Murata et al, 2020). Walker et al found that cancer-induced systematic inflammation played an important role in cognitive impairment (Walker et al, 2018). The brain tumour induced inflammation, especially in the peri-tumour brain region, has resemblances with these.…”
Section: Discussionmentioning
confidence: 99%
“…The role of inflammation in Alzheimer disease (AD) and some psychological disorders has been studied much deeper than in other fields (Heppner et al et al, 2015;Murata et al, 2020). Walker et al found that cancer-induced systematic inflammation played an important role in cognitive impairment (Walker et al, 2018). The brain tumour induced inflammation, especially in the peri-tumour brain region, has resemblances with these.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, aspirin administration via drinking water has been used in other murine disease models before. [43][44][45][46] Our results suggest that low-dose aspirin represents an effective tumor-preventive agent in the context of inflammation-associated colon tumorigenesis. In the AOM model for sporadic colon tumor development, the aspirin-induced reduction in tumor incidence was still significant, but with a less marked effect, while in the APC Min/+ model aspirin treatment failed to show significant tumor-preventive efficacy.…”
Section: Discussionmentioning
confidence: 66%
“…Administration in the drinking water makes assessment of exact dose difficult per mouse, however, we tried to control for this by (a) comparing the COX‐1 inhibitory effect of the drinking water administration with gavaging at a dose of 25 mg/kg in initial pharmacodynamic dosing experiments (Figure ; Table ); and (b) by regular control of the consumed drinking water volume that mice achieved a similar dose. Moreover, aspirin administration via drinking water has been used in other murine disease models before …”
Section: Discussionmentioning
confidence: 99%
“…The different results for aspirin and non-aspirin NSAIDs are also biologically plausible. Accumulating evidence supports the role of COX-1 inhibition in attenuating neuroinflammation, leading to protection against inflammatory brain damage [28,38,39]. In contrast, COX-2 inhibitors have been shown to augment nitro-oxidative and oxidative stress in the brain [40], and to interfere with the resolution of inflammation by Table 4 Hazard ratios (95% confidence intervals) of depression, anxiety, and stress-related disorders during the year after cancer diagnosis in relation to pre-diagnostic exclusive use of aspirin, stratified analysis by different factors (Continued) The columns refer to four definitions of exposure in separate models: any exclusive use of aspirin, current use of aspirin, low-dose use of aspirin, and long-term use of aspirin, where no use of NSAIDs was used as the reference in all models.…”
Section: Discussionmentioning
confidence: 97%
“…There is, however, a lack of evidence in this regard among cancer patients and on psychiatric disorders other than depression. Our recent preclinical study showed that low-dose aspirin might counteract the inflammation-related cognitive impairment in a mouse model of breast cancer [28]. It is therefore plausible that aspirin may help to prevent inflammation-related psychiatric disorders among cancer patients.…”
Section: Introductionmentioning
confidence: 99%